Geografija v Evropi in na Slovenskem v času velikih geografskih odkritij - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2019)
The paper presents the development of European and Slovenian geography at the time of the great geographical discoveries between the 15th and the end of the 18th century. During this period geographical horizons were remarkably widened, and a huge amount of information about the world was gathered which prompted the need for new ways of processing and displaying the knowledge of the Earth's surface. During this time, the number of cartographic illustrations of today's Slovenian territory increased. Some personages who contributed to the pro-gress of European science and to better knowledge of the world lived in Slovenia or originated from this territory.
Keywords: geografska odkritja; geographical discoveries; history of geography; predhodniki moderne geografije; Slovene geography; slovenska geografija; zgodovina geografije